The Effect of Using Blended Learning Model on Enhancing Students' Speaking Skills in Senior High Schools - Irma Dewi Isda; Purwati Purwati; Imran Imran (Universitas Pendidikan Mandalika, 2021)
This study aimed at investigating the effect of blended learning on the English-students’ speaking skills at SMAN 2 Patra Nusa Aceh Tamiang. Also, this study investigated students’ level differences of English-speaking skills of SMA Patra Nusa students. Twenty-five students of the eleventh-grade class were involved in this study. This study used a quasi-experimental with pre-experimental design. The instruments used in this study were observation and test (pretest and posttest). The results of data analysis showed that sig. 2-tailed = 0.000 < α (0.05), it means reject H0, accepted Ha. Finding obtained of pretest 77,04 and posttest 88,95. In conclusion, the mean pretest and posttest scores differ significantly. In other words, blended learning positively affects students speaking skills used in the media google classroom at SMA N 2 Patranusa.